Pengaruh Tingkat Pendidikan, Disiplin Kerja Terhadap Produktivitas Karyawan Bagian Produksi di PT. Kahatex - Lisnawati, Lisnawati; Wijaya, Fanji (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aimed to determine whether the level of education and work discipline affect the productivity of production employees at PT Kahatex. This research method uses quantitative with a descriptive and verification method approach; the sample in this study was 86 employees of the production department of PT Kahatex. The study's results showed that partially or the T-test of the Education Level variable had a positive and significant effect on the Employee productivity variable; this can be seen from the T count of 4.622 <1.992 T table with a sig level of 0.00 <0.05. The Work Discipline variable has a positive and significant effect on the Employee productivity variable; this can be seen from the T count of 6.579 <1.992 T table with a sig level of 0.00 <0.05. While together or through the F Test, the variables of Education Level and Work Discipline simultaneously significantly affect Employee productivity; this can be seen from the results of the F count of 35.725> 2.71 F table with a significance value of 0.000 <0.05. From the results of the validation of the lowest productivity values, namely 0.485, 0.476, and 0.477, here, the company PT Kahatex must be able to increase the results or output achieved by its employees and must be able to make production targets more efficient. Validation of the variables of the lowest education level values is 0.452 and 0.484; here, PT Kahatex employees must be able to improve the formal education of certain employees so that they have the knowledge and skills to carry out their duties properly. While the variable of work discipline with the lowest validation results of 0.317, 0.485, and 0.386 is still lacking in employee discipline, the company PT Kahatex must increase the level of attendance and ethics because the better the employee's work discipline, the higher the performance that will be achieved by production employees.